Diabetes self-care and its associated factors among type 2 diabetes mellitus with chronic kidney disease patients in the East Coast of Peninsular Malaysia - Ramli,Siti Aisyah; Draman,Nani; Muhammad,Juliawati; Mohd Yusoff,Siti Suhaila (PeerJ, 2024)
Introduction Diabetes self-care among diabetic patients is crucial as it determines how patients care for their illness in their daily routine for better diabetes control. This study aims to calculate the average score for diabetes self-care among patients with type 2 diabetes mellitus and chronic kidney disease and to identify factors that are associated with this score. Materials and Methods This cross-sectional study enrols patients over 18 years old with type 2 diabetes mellitus and chronic renal disease with an eGFR of less than 60 mL/min/1.73 m2 in a tertiary hospital in Malaysia. The Malay version of the Summary of Diabetic Self-Care Activities (SDSCA) was used to assess diabetes self-care, the Malay version of the diabetes-related distress questionnaire (DDS-17) was used to assess diabetes distress, and the Malay version of the Patient Health Questionnaire-9 (PHQ-9) was used to assess depression. Data analysis was performed using both simple and multiple linear regression models to determine the associations between variables. Result One hundred and seventy-six eligible patients were recruited for this study. The mean score for diabetes self-care is 3.62. The eGFR (p = 0.002) and diabetes distress (p = 0.004) are the significant associated factors for diabetes self-care among type 2 diabetes mellitus patients with chronic kidney disease. Conclusion The mean score for diabetes self-care indicated a moderate level of self-care. The eGFR level and diabetes distress were important factors influencing diabetes self-care practices.
Keywords: Diabetes self-care; Chronic kidney disease; Depression; Type 2 diabetes mellitus; Estimated glomerular filtration rate (egfr)